1993
DOI: 10.1080/09500349314550721
|View full text |Cite
|
Sign up to set email alerts
|

Lamellar Gratings as Polarization Components for Specularly Reflected Beams

Abstract: High spatial frequency lamellar gratings are shown to function as phase compensators, quarter-wave and half-wave retarders, and polarization rotators that operate on specularly reflected (zeroth-order) beams . These gratings are designed using rigorous coupled-wave and modal grating diffraction theories . Controlling the geometrical parameters of these gratings allows for engineering the phase retardation and polarization conversion introduced to a reflected beam . Fabrication and operational tolerances for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…A quarter-wave retarder is obtained when h/A = 0.155 and a half-wave plate is obtained when h/A = 0.215. Use of oblique or conical incidence is also possible [1,2]. 6 Guided-mode resonance filters Narrow-band reflectors may be realized by combining a subwavelength-period grating with a waveguide structure [13].…”
Section: Grating Retardersmentioning
confidence: 99%
See 1 more Smart Citation
“…A quarter-wave retarder is obtained when h/A = 0.155 and a half-wave plate is obtained when h/A = 0.215. Use of oblique or conical incidence is also possible [1,2]. 6 Guided-mode resonance filters Narrow-band reflectors may be realized by combining a subwavelength-period grating with a waveguide structure [13].…”
Section: Grating Retardersmentioning
confidence: 99%
“…We will consider briefly both the fascinating potential applications of subwavelength-period gratings and the challenge of their fabrication. More complete treatments of the theoretical aspects of subwavelength-period gratings may be found in recent and forthcoming books [1,2]. 2 Theoretical models for subwavelength-period gratings We will consider in this paper mainly lamellar diffraction gratings of depth h, with a refractive-index distribution of the form n(x) = fli when 0 < x < C and n(x) = 2 when c < x < d. Here d is the grating period and the indices ni and n2 may, in general, be complex.…”
Section: Introductionmentioning
confidence: 99%
“…The behaviour of the phases in other experiments involving metallic surfaces [7,9,10], has not only theoretical interest, since it clearly evidences the resonant nature of the coupling between photons and surface plasmons, but also gives rise to interesting interferometric applications . Recent studies on phase properties of diffracted light include the case of reflection and transmission gratings in classical mountings [11] and the case of high spatial frequency lamellar grating in conical mountings [12] .…”
Section: Introductionmentioning
confidence: 99%
“…In (B-10) and the inner products are those defined in (28) and (37), and the subscript s indicates that the weight function o ¢') should be used in the integral. By using (55) and (47), it can be shown that the two sub-matrices in (8)(9)(10)(11) …”
Section: Appendix Bmentioning
confidence: 99%
“…In many applications, lameUar gratings are used in conical mountings [11]. Recently, a modal analysis of lamellar gratings in conical mountings was presented by Peng [12].…”
Section: Introductionmentioning
confidence: 99%